2022
DOI: 10.3390/healthcare10112285
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice towards Evidence-Based Medicine among Northern Saudi Primary Care Physicians: A Cross-Sectional Study

Abstract: The evidence-based practice of primary care physicians is essential because they are the first line of contact with the local community, and they cater to most of their communities’ health needs. In the current study, in which we used a cross-sectional survey in northern Saudi Arabia, we assessed primary care physicians’ knowledge, attitude, practice, and barriers regarding evidence-based medicine (EBM). Of the 300 physicians who participated, less than half had high knowledge (43.7%) and attitude (47.7%) towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…As regards to the participants' knowledge of different EBM resources, nearly half of the participants (47.3%) knew about EBM from BMJ. This result showed a higher awareness regarding EBM from BMJ than the investigation of Abd AL-Magied et al (12) (Menoufia Governorate, Egypt) and Hassan et al (10) (Benha, Egypt) wherein just 28.6% and 27.3% of respondents, respectively, indicated knowledge of that resource (16,17) but unlikely it was lower than that obtained by Al-Kubaisi et al (20) (Doha, Qatar), Abdel-Kareem et al (9) (Tanta, Egypt) and Dabaghian et al (19) (Iran), in which 69.2%, 60.5% and 60.1%, respectively reported awareness of that resource. Additionally, 11.3% of participants reported they have previously made decisions using EBM from BMJ.…”
Section: Awareness Of Different Ebm Resourcesmentioning
confidence: 51%
See 4 more Smart Citations
“…As regards to the participants' knowledge of different EBM resources, nearly half of the participants (47.3%) knew about EBM from BMJ. This result showed a higher awareness regarding EBM from BMJ than the investigation of Abd AL-Magied et al (12) (Menoufia Governorate, Egypt) and Hassan et al (10) (Benha, Egypt) wherein just 28.6% and 27.3% of respondents, respectively, indicated knowledge of that resource (16,17) but unlikely it was lower than that obtained by Al-Kubaisi et al (20) (Doha, Qatar), Abdel-Kareem et al (9) (Tanta, Egypt) and Dabaghian et al (19) (Iran), in which 69.2%, 60.5% and 60.1%, respectively reported awareness of that resource. Additionally, 11.3% of participants reported they have previously made decisions using EBM from BMJ.…”
Section: Awareness Of Different Ebm Resourcesmentioning
confidence: 51%
“…(19) . However higher results obtained by ALruwaili et al (16) (Saudi Arabia), which revealed that 49% of participants were aware of database of reviews and dissertations. This variance may be due to more than two thirds of the Saudi and non-Saudi participants (61.7%) attended training in EBM while in this study only (37.3%) of the participants attended previous EBM training.…”
Section: Awareness Of Different Ebm Resourcesmentioning
confidence: 64%
See 3 more Smart Citations